Implementación de un sistema de control automatizado para un intercambiador de calor de tubos concéntricos, para el desarrollo práctico de los sistemas de control de lazo cerrado y abierto por medio de protocolo de comunicación modbus-rtu. - Mahecha Guerra, Jeisson Humberto (Universidad Antonio Nariño, 2021)
The purpose of this project is to implement an automated control system applied to a concentric tube exchanger at the Antonio Nariño University, integrating an-output water temperature control loop and a control loop to drive the actuators involved in the system. The search and investigation of the operation of the concentric tube exchanger allows the theoretical characterization of the transfer function in order to apply the appropriate control system, in addition to its rapid response to external output perturbations, for subsequent application in the internal programming of the PLC. Likewise, under this research, the tanks that will contain the hot and cold water will be designed, in addition to the piping system and measurement points of the temperature variables to be intervened, which can be viewed through a real-time interface and graphically on the HMI screen. Consequently, an industrial communication protocol MODBUS-RTU is established with the RS-485 communication standard, for monitoring and manipulating the state of the temperature variables in conjunction with the actuators, serving as the HMI display master. Through the implemented control loops, as well as the manipulation, operation and physical calibration of the device, two guides are prepared to start the equipment, in addition to the step by step to establish a communication protocol taking into account It has the general aspects necessary for the configuration of the DELTA brand equipment. Finally, the implementation of the automated control system for the exchanger can be evidenced, displaying temperature variables at the inlet and outlet, obtaining the transfer function of the system in a practical way, modifying the gains obtained under the control implementation procedures PID, data collection and system analysis.